Polysemy in the Semantic Field of Movement in the English Language - Isabel Negro Alousque (Miscelánea: A Journal of English and American Studies, 2000)
In this paper we will attempt to demonstrate that the lexicon is not neatly divided through the analysis of the semantic field of MOVEMENT in the English language. We will first describe the model of lexical description that we have followed, the Functional-Lexematic Model (Martín Mingorance, 1984), which consists of three levels of analysis: the paradigmatic, syntagmatic and cognitive axes. Then we will examine the double/ multiple membership of MOVEMENT verbs within their semantic field (intrafield membership) and across the lexicon (interfield membership). Intrafield membership is determined by three factors: focalization of a meaning component, genus of the lexeme, and metaphorical extension of the lexical unit. Interfield membership is accounted for by metaphorical processes.